Implementasi Etika Bisnis Islam Dalam Produksi Di Home Industri Tiga Bintang Kerang-Sukosari-Bondowoso - Nurul Hamidah; Nihayatut Tasliyah; Sukandi Sukandi (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2023)
This Tiga Bintang Home Industry has used Islamic business ethics, in accordance with the Islamic ethics that have been implemented by the leaders of the Tiga Bintang Home Industry. Therefore, the Tiga Bintang Home Industry has been confirmed to be good at producing it. With this Three Bintang Home Industry, it provides good service and the people around the Tiga Bintang Home Industry feel the benefits. This study aims to answer the question, how is the Implementation of Islamic Business Ethics in the production of Tape Tiga Bintang Kescal Sukosari Bondowoso and what are the factors that become obstacles in production. Tape Three Stars Shells Sukosari Bondowoso. The research method used is field research or commonly called qualitative research. Data collection techniques used are interviews, direct observation of production activities, and documentation. The research results obtained are that the Tiga Bintang Home Industry Tape has implemented Islamic ethical principles in its production activities, namely: ihsan, itqon, faith, taqwa, istiqomah and maslahah and working in a halal field but an ethical barrier that is not optimally applied. Namely, istiqomah because raw materials are an obstacle to the production factor, the Three Star Tape home industry, and there are supporting factors that are a separate guideline for the three star home industry, namely good human resources, that is what makes this Home Industry more and more customers and growing because it is careful in choosing HR, so it is really good in terms of Management, Service and Implementing Islamic Ethical Values.